Roles of the Wnt Signaling Pathway in Head and Neck Squamous Cell Carcinoma - Xie, Jing; Huang, Li; Lu, You-Guang; Zheng, Da-Li (Frontiers in Molecular Biosciences, 2021)
Head and neck squamous cell carcinoma (HNSCC) is the most common type of head and neck tumor. It is a malignant tumor with high incidence and is associated with a low survival rate, and there are limited treatment options. Accumulating evidence indicates that the Wnt signaling pathway plays an important role in the pathobiological process of HNSCC. The canonical Wnt/β-catenin signaling pathway affects a variety of cellular processes, enabling tumor cells to maintain and expand the immature stem-like phenotype, proliferate, prolong survival and gain invasiveness. Genomic studies of head and neck tumors have shown that although β-catenin is not frequently mutated in HNSCC, its activity is not inhibited by mutations in NOTCH1, FAT1, and AJUBA, the upstream regulators encoding β-catenin. Genetic defects affect the components of the Wnt pathway in oral squamous cell carcinoma and the epigenetic mechanisms that regulate inhibitors of the Wnt pathway. This paper aims to summarize the groundbreaking discoveries and recent advances involving the Wnt signaling pathway in cancer. In addition, this paper aims to highlight the relevance of this pathway to head and neck squamous cell carcinoma, which will help provide new insights into improving the treatment of human head and neck squamous cell carcinoma by interfering with the transcriptional signaling of Wnt.